2014
DOI: 10.15388/omee.2014.5.1.14239
|View full text |Cite
|
Sign up to set email alerts
|

Empowering Women Entrepreneurs in Emerging Economies: a Conceptual Model

Abstract: Cyberfeminism is a woman-centered perspective that advocates women’s use of new information and communications technologies for empowerment. This paper explores the role of information technologies, in particular the role of social media, in empowering women entrepreneurship in emerging economies via increased social capital and improved self-efficacy. A conceptual model is offered and propositions are explicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 52 publications
(38 reference statements)
2
25
0
Order By: Relevance
“…In economic sectors, Ajjan et al [15] proposed a conceptual model based on the concepts of social capital and self-efficacy to examine the use of social media in empowering women entrepreneurs in emerging country. The model was then tested by Beninger et al [3] who found that social media has an overall positive impact on the lives of women entrepreneurs in Egypt, both personally and professionally.…”
Section: B Social Media and Women-preneur Empowermentmentioning
confidence: 99%
“…In economic sectors, Ajjan et al [15] proposed a conceptual model based on the concepts of social capital and self-efficacy to examine the use of social media in empowering women entrepreneurs in emerging country. The model was then tested by Beninger et al [3] who found that social media has an overall positive impact on the lives of women entrepreneurs in Egypt, both personally and professionally.…”
Section: B Social Media and Women-preneur Empowermentmentioning
confidence: 99%
“…Phone users with higher levels of education are more likely to interact more regularly through social media than those with lower levels of education [5]. ICT access escalates higher efficiency, productivity, faster information sharing among employees, and supports creation and transfer of knowledge that enhances collaboration and communication due to faster transfer of information [36,37]. According to research, social media usage by women entrepreneurs in emerging economies increases a woman's self-efficacy and social capital [38].…”
Section: Social Media Usage and Benefitsmentioning
confidence: 99%
“…Blogging has helped them to run a campaign against gender inequality and male domination of employment opportunities. Furthermore, Ajjan, Beninger and Mostafa note that social media platforms are not only giving women a voice to challenge the various aspects of discrimination, they have also offered a variety of ways in which Iranian women entrepreneurs can source and distribute information (Ajjan et al, 2014).…”
Section: Gm 351mentioning
confidence: 99%